A Study on the Effects of Franchising' on Entrepreneurship in Elazig-Malatya Provinces - Gözüaçık, Seren; Demir, Özcan (Fırat University, 2019)
The main purpose of this study is to examine how the franchisee entrepreneurs perceive the franchise system and how these perceptions affect entrepreneurship. For this purpose, the universe of the research is composed of the companies which are businesses receiving franchise in Elazığ and Malatya province center in 2018. The number of participants in the various sectors (food, clothing, education), that is, the universe of research are 148 people. In this study, the quantitative research method has been used and data obtained through the face-to-face survey technique. The questionnaires were distributed to the participants by hand and filled with face-to-face interviews. SPSS-22 program was used for data analysis. Descriptive statistical methods such as number, percentage, mean, and standard deviation were used to evaluate the data. In our study, t-test was used to compare quantitative continuous data between two independent groups and One-way Anova test was used to compare quantitative continuous data between two independent groups. In our study according to the findings of the research is concluded a significant difference with the perceptions of the entrepreneurs on the gender, age, educational status and previous occupations between the reasons for participation in the franchise process and operation.and reasons for orientation to franchise system, the difficulties of obtaining franchises, the reasons that affect the franchise, the reasons for participation in the franchise process and operation.

Bu çalışmanın temel amacı, franchise alan girişimcilerin franchise sistemini nasıl algıladıkları ve bu algılamalarının girişimciliğe ne gibi etkisi olduğunun araştırılmasıdır. Bu amaçla araştırmanın evrenini olarak 2018 yılında Elazığ ve Malatya İl merkezindeki franchise alan işletmeler oluşturmaktadır. Çeşitli sektörlerde (gıda, giyim, eğitim) ulaşılan katılımcı sayısı yani araştırmanın evreni 148 kişidir. Çalışmada nicel araştırma yöntemi kullanılmış ve veriler yüz yüze anket tekniği ile elde edilmiştir. 148 katılımcıların tamamına anket elden dağıtılmış ve yüz yüze görüşmede doldurulmuştur. Verilerin analizinde SPSS-22 programı kullanılmıştır. Verilerin değerlendirilmesinde tanımlayıcı istatistiksel yöntemleri olarak sayı, yüzde, ortalama, standart sapma kullanılmıştır. İki bağımsız grup arasında niceliksel sürekli verilerin karşılaştırılmasında t-testi, ikiden fazla bağımsız grup arasında niceliksel sürekli verilerin karşılaştırılmasında Tek yönlü (One way) Anova testi kullanılmıştır. Araştırma bulgularına göre, girişimcilerin cinsiyet, yaş, öğrenim durumu ve önceki meslekleri değişkenleri ile franchise sistemine yönelim nedenlerine ilişkin algıları, franchise alma zorluklarına ilişkin algıları, franchise almaya etken olan sebeplere ilişkin algıları ve franchise süreci ve işleyişine katılım nedenlerine ilişkin algıları arasında anlamlı farklılık olduğu sonucuna ulaşılmıştır.
FRANCHISING’IN GİRİŞİMCİLİK ÜZERİNDEKİ ETKİLERİ ÜZERİNE ELAZIĞ-MALATYA İLLERİNDE BİR ÇALIŞMA